Phase shifters with multiple independently controllable bands utilising frequency‐selective variable gain networks. Issue 2 (4th January 2021) - Venter, Johannes J. P.; Stander, Tinus
Abstract: A dual‐band vector‐sum phase shifter with independent phase control of the 2.4 and 5 GHz Wi‐Fi bands is presented. The network uses band‐limited variable gain amplification, with a broadband hybrid coupler at the input and an in‐phase recombiner at the output. The circuit is prototyped on RF printed circuit board and exhibits performance characteristics comparable to the state‐of‐the‐art single band vector‐sum phase shifters. The prototype achieved an average gain of 2.16 dB over the 2.4 GHz band, with less than 0.26 dB and 1.32° root‐mean‐square (RMS) gain and phase error across all 2.4 and 5 GHz band tuning states. In the 5 GHz band, an average gain of 0.17 dB is achieved, with less than 0.21 dB and 3.88° RMS gain and phase error. The network's ability to generate band‐independent vector modulation over a 12 dB/90° tuning range is demonstrated as well, achieving less than 0.12 dB and 0.27° RMS gain and phase error in the 2.4 GHz band, and less than 0.27 dB and 2.94° gain and phase error in the 5 GHz band.